2010
DOI: 10.1371/journal.pone.0012524
|View full text |Cite
|
Sign up to set email alerts
|

α2,3-Sialyltransferase ST3Gal III Modulates Pancreatic Cancer Cell Motility and Adhesion In Vitro and Enhances Its Metastatic Potential In Vivo

Abstract: BackgroundCell surface sialylation is emerging as an important feature of cancer cell metastasis. Sialyltransferase expression has been reported to be altered in tumours and may account for the formation of sialylated tumour antigens. We have focused on the influence of alpha-2,3-sialyltransferase ST3Gal III in key steps of the pancreatic tumorigenic process.Methodology/Principal FindingsST3Gal III overexpressing pancreatic adenocarcinoma cell lines Capan-1 and MDAPanc-28 were generated. They showed an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 69 publications
11
77
0
Order By: Relevance
“…Although all PDA cell lines expressed both types of SA receptors on their surfaces, differences in expression levels were noted. Such heterogeneity in levels of SA expression in different cell lines was not surprising, as altered levels of expression of sialyltransferases and fucosyltransferases have been demonstrated in different types of tumors, including pancreatic, breast, colon, gastric, cervical, and renal cancers (47,48). Similar results have also been observed in the case of melanoma cell lines, with heterogeneous distribution of surface receptors when different lines were compared (49).…”
Section: Discussionsupporting
confidence: 56%
“…Although all PDA cell lines expressed both types of SA receptors on their surfaces, differences in expression levels were noted. Such heterogeneity in levels of SA expression in different cell lines was not surprising, as altered levels of expression of sialyltransferases and fucosyltransferases have been demonstrated in different types of tumors, including pancreatic, breast, colon, gastric, cervical, and renal cancers (47,48). Similar results have also been observed in the case of melanoma cell lines, with heterogeneous distribution of surface receptors when different lines were compared (49).…”
Section: Discussionsupporting
confidence: 56%
“…Some authors reported the higher immunoreactivity of the enzyme a-2,6-sialyltransferase in well differentiated tumors (e.g. in hepatic cell carcinoma [21]), but others found the a-2,6-GalST immunoexpression to be more prevalent in tumors of higher histological grade (colorectal cancer [11], pancreatic cancer cell line [12]). The same concerns the influence of on cellular motility and invasive capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have found a-2,6-GalSA to be associated with cell differentiation and proliferation [7], intercellular and cell-matrix interactions [8] and immunity [9]. Their role in cancer has not yet been fully established, although available studies tend to demonstrate it as an indicator of poor prognosis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant sialylation is correlated with increased motility of cancer cells and promotes metastasis (6,18,21). This prompted us to evaluate the potential of P-3F ax -Neu5Ac to alter the migratory capacity of B16F10 cells.…”
Section: P-3f Ax -Neu5ac Treatment Impairs Binding To Ecm Components mentioning
confidence: 99%
“…Hypersialylation (a2,6) of a1b1 integrin enhances binding to collagen type I and favors cancer cell migration (20). P erez-Garay and colleagues reported that ST3Gal-III-overexpressing pancreatic adenocarcinoma cells formed metastatic lesions and drastically decreased survival in mice (21).…”
Section: Introductionmentioning
confidence: 99%